2005
DOI: 10.1007/s00429-005-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Localization of alkaline phosphatase and proteins related to intercellular junctions in primary cultures of fetal rat hepatocytes

Abstract: The localization of alkaline phosphatase (ALP) and four proteins related to intercellular junctions in primary cultures of fetal rat hepatocytes was immunocytochemically investigated using fluorescence-labeled antibodies and confocal laser microscopy in order to determine whether the formation of intercellular junctions at the borders between adjacent rat hepatocytes becomes the trigger of translocation of ALP from the cytoplasm to the plasma membrane. Dexamethasone (DEX) which was supplemented in the base med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…1B). We previously demonstrated that the long stretches of plasma membrane exhibiting ALP localization between cell borders of normal hepatocytes are those surrounding the bile canaliculus-like structure, as the bile canaliculus marker occludin is colocalized in these long stretches of plasma membrane [5]. On the other hand, CAPD was observed in small scattered dots in the cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1B). We previously demonstrated that the long stretches of plasma membrane exhibiting ALP localization between cell borders of normal hepatocytes are those surrounding the bile canaliculus-like structure, as the bile canaliculus marker occludin is colocalized in these long stretches of plasma membrane [5]. On the other hand, CAPD was observed in small scattered dots in the cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that, in monolayer culture systems, adult rat hepatocytes cultured on a single collagen gel rapidly dedifferentiate, but cells sandwiched between two layers of collagen gel maintain cellular morphology and function for long periods [ 18 , 21 ]. However, in the present culture system of fetal rat hepatocytes, dexamethasone induced GGT translocation, the formation of bile canaliculus-like structures and the appearance of connexin 32 at cell borders [ 6 , 10 , 13 ]. The above results coincided with those reported in primary rat hepatocytes overlaid with a basement membrane-like matrix extracted from Engelbreth-Holm-Swarm mouse tumor [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) in rat hepatocytes is mainly localized in the plasma membrane surrounding the bile canaliculus [ 1 , 4 , 14 , 33 , 34 ] and hydrolyzes the phospholipids in bile excreted by hepatocytes into the bile canalicular lumen [ 27 ]. Previous papers have reported that dexamethasone, in primary cultures of fetal rat hepatocytes, promotes formation of the bile canaliculus-like structure [ 6 ] and translocation of ALP from the limited perinuclear cytoplasm to the plasma membrane surrounding the bile canaliculus-like structure [ 10 , 13 ]. Moreover, in the same culture system, it was demonstrated that dexamethasone represses DNA synthesis [ 6 ] and promotes the appearance of connexin 32 between adjacent hepatocytes [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, glucocorticoids enhance Cx32 expression in primary cultured rat hepatocytes and MH 1 C 1 rat hepatoma cells [17]. Our previous study of primary cultured fetal rat hepatocytes demonstrated that dexamethasone (DEX) induces the formation of bile canaliculus-like structures (BCLS), the localization of alkaline phosphatase (ALP) in the plasma membrane around BCLS, and the expression of Cx32 along the borders between adjacent cells [6, 8, 9]. However, we have not yet demonstrated whether Cx32 expression is related to BCLS and the localization of ALP in fetal rat hepatocytes.…”
Section: Introductionmentioning
confidence: 99%